Discursive representations of restorative justice in international policies - Pali, Brunilda (European journal of criminology, 2023)
The European Directive 2012/29/EU establishing minimum standards on the rights, support and protection of victims of crime, the Council of Europe Recommendation CM/Rec(2018)8 concerning restorative justice in criminal matters, and the recently updated United Nations Handbook on Restorative Justice Programmes testify to the increasing policy recognition of restorative justice at the international level. And yet, despite the vast and burgeoning literature on restorative justice, limited research and critical analysis have been conducted on policies, and even less on international policies and instruments. As a result, we know little about how restorative justice is framed within policy and how such framings could contribute towards the development of this field in practice. Addressing this gap, this article seeks to understand the ways in which restorative justice is construed within international policies and their conditions of possibility, using a ?policy-as-discourse? analytical approach. The article also elicits implications for the study of the relationships between restorative justice policy and practice and for future research on the institutionalization of this ?new? frontier of penality internationally.